Comparative and Phylogenetic Analysis of the Complete Chloroplast Genomes of Three Paeonia Section Moutan Species (Paeoniaceae) - Wu, Liwei; Nie, Liping; Xu, Zhichao; Li, Pei; Wang, Yu; He, Chunnian; Song, Jingyuan; Yao, Hui (Frontiers in Genetics, 2020)
Analysis of the relationships among wild species of section Moutan in the plant genus Paeonia has traditionally been problematic. Interspecies relationships cannot be effectively determined using phenotypic traits alone, or through analysis of nuclear or chloroplast DNA fragments. Elucidation of complete chloroplast genome sequences will aid the identification and phylogeny of these species. In this study, the complete chloroplast genomes of three sect. Moutan plants were sequenced and analyzed. Comparative and phylogenetic analyses of the complete chloroplast genomes of all eight species of sect. Moutan were then conducted. The three complete chloroplast genomes gained in this study showed four-part annular structures, and the genome length, structure, GC content, codon usage, and gene distribution were highly similar. There was greater variation in the noncoding regions of the sequences than in the conserved protein-coding regions. Sequence variations in the small single copy (SSC) regions and large single copy (LSC) regions were considerably greater than those in the inverted repeat (IR) regions. Phylogenetic analysis revealed that the species of sect. Moutan clustered in one branch and then subdivided into smaller branches. As for the three complete chloroplast genome sequences obtained in this study, Paeonia jishanensis clustered with another P. jishanensis sequence from the GenBank database, P. qiui clustered with P. rockii, and P. delavayi var. lutea clustered with P. ludlowii. It was also found that the complete chloroplast genomes, LSC regions, and SSC regions all showed great abilities in identification and phylogenetic analysis of the species of sect. Moutan, while IRs regions and highly variable regions were not suitable for the species of sect. Moutan.